Knights of the Golden Rule : The Intellectual as Christian Social Reformer in the 1890s - Frederick, Peter J. (Book collections on Project MUSE., 1976)
This is a book about American intellectuals as would-be social reformers and what happens to them in the arena of practical politics. Specifically, it examines the lives of ten highly idealistic Christian socialist and anarchist intellectuals of the 1890s who were profoundly influenced -- indeed inspired -- by the prophetic social messages and exemplary lives of Tolstoy, Mazzini, and Ruskin. The ten Americans -- including ministers, journalists, professors, and poets -- were constantly thwarted in their efforts to apply the Golden Rule and the ethics of Jesus not only to the socioeconomic inst.